2012
DOI: 10.1111/j.1440-1819.2012.02351.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved outcomes following a switch to olanzapine treatment from risperidone treatment in a 1‐year naturalistic study of schizophrenia patients in Japan

Abstract: Aims: This study assessed clinical and functional outcomes following a switch from risperidone to olanzapine in a 1-year naturalistic study of schizophrenia patients in Japan. Methods:We used data from a large 1-year prospective, multicenter, observational non-interventional study of individuals who were initiated on olanzapine for the treatment of schizophrenia in Japan. Current analyses focused on patients who were switched at study entry from risperidone to olanzapine (n = 258). Repeated measures analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“… 55 Fourteen studies in our review reported on the duration of the illness. 20 , 21 , 23 , 24 , 30 , 34 , 36 , 37 , 42 , 44 , 46 , 52 , 56 , 61 A comparison of the employment rates and the duration of the disorder between these studies did not show a consistent pattern of declining rates with longer duration of the disorder. For example, McCreadie 44 reported an employment rate of 8% in study participants, with an average duration of 8 years, while Middelboe et al 46 reported an employment rate of 12% in participants, with an average duration of 15 years.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“… 55 Fourteen studies in our review reported on the duration of the illness. 20 , 21 , 23 , 24 , 30 , 34 , 36 , 37 , 42 , 44 , 46 , 52 , 56 , 61 A comparison of the employment rates and the duration of the disorder between these studies did not show a consistent pattern of declining rates with longer duration of the disorder. For example, McCreadie 44 reported an employment rate of 8% in study participants, with an average duration of 8 years, while Middelboe et al 46 reported an employment rate of 12% in participants, with an average duration of 15 years.…”
Section: Resultsmentioning
confidence: 84%
“…No study was found exclusively focusing on inpatients. Only in the study of Ye et al 61 were figures of employment rates for in-and outpatients separately presented. Both the baseline and follow-up employment rates in persons treated as outpatients were almost four times higher in comparison with the rates among inpatients.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Roussidis and colleagues showed that switching a patient’s antipsychotic medication for reasons related to lack of efficacy and/or tolerability was associated with a significantly improved clinical benefit and increased adherence to treatment [ 74 ]. Similarly, studies of patients switching to olanzapine [ 28 ], quetiapine [ 29 , 34 ], ziprasidone [ 33 , 75 ], aripiprazole [ 76 ], long-acting injectable risperidone [ 32 , 77 ], or paliperidone [ 36 ] have reported improvements in cognitive function, psychotic symptoms, and/or tolerability during up to one year of treatment. However, the current analysis is the only switch study to examine long-term changes in subjective responses, tolerability, adherence-related attitude, and HRQoL using the disease-specific PETiT assessment.…”
Section: Discussionmentioning
confidence: 99%
“…[10] In a 1 year naturalistic study, a significant number of patients who switched from risperidone to olanzapine experienced significant improvement in clinical and functional outcomes. [11] A Cochrane review concluded that olanzapine improved the general mental state (total positive and negative syndrome scale [PANSS] score) better than risperidone. [12]…”
Section: Introductionmentioning
confidence: 99%